Influence on off-gassing during storage of Scots pine wood pellets produced from sawdust with different extractive contents. (January 2022) - Siwale, Workson; Frodeson, Stefan; Berghel, Jonas; Henriksson, Gunnar; Finell, Michael; Arshadi, Mehrdad; Jonsson, Carina
Abstract: Off-gassing and self-heating are the major challenges when it comes to transportation and storage of wood pellets. The heat generated due to self-heating poses a fire risk while off-gassing of toxic gasses such as carbon monoxide (CO) and some volatile organic compounds (VOCs) is an environmental and human health risk. With the increase in production volumes of wood pellets which has subsequently increased the amounts of wood pellets in transportation and storage, there is need to find lasting solutions to off-gassing and self-heating of wood pellets. The objective of this study was to test the off-gassing abilities of Scots pine wood pellets produced from sawdust with varying amounts of extractives. The aim is to come up with raw material pre-treatment measures so as to produce wood pellets that are not liable to off-gassing. Six (6) types of sawdust raw materials namely; fresh pine sawdust (FPS), stored pine sawdust (SPS), sawdust plus pine rosin (PRS), sawdust plus linseed oil (LOS), sawdust plus tall oil (TOS) and acetone extracted sawdust (AES) were used to produce the pellets. The produced pellets were then subjected to off-gassing tests under controlled conditions using the ECOM J2KN analyser. The concentrations of carbon monoxide, carbon dioxide and methane increased with storage time but slowed down towards the end of the nine days test period. The formation of these gasses were largely dependent on the type of extractives present in the raw material and not the total extractive content. The formation of methane started later than the other gases and coincided with the time when residual oxygen was depleted. Highlights: Off-gassing of wood pellets is influenced by the type of extractives in the raw material and not the total extractive. The concentration of off-gasses increases with storage time up to a certain extent. Stored and acetone extracted pellets lost the ability of fresh pine wood pellets to form gas emissions. Methane formation in off-gassing of wood pellets is strongly dependent on anaerobic conditions.